Influence of Education Level, Training and Compensation Against Nurse Performance at UIT Hospital Makassar - Hajar Nur Aswad; Eddyman Feriyal (STIE AMKOP, 2016)
The purpose of this research are: 1) to know the effect of education on employee performance, 2) to know the effect of training on employee performance, 3) to know the effect of compensation on nurse's performance, and 4) to know which is most significant partially to nurses performance in UIT Makassar Tourist Hospital. The research method is taken from the interview. Data from case group came from data of UIT Makassar Tourism General Hospital. Respondent Criteria consisted of inclusion and exclusion method with number of sample member counted 70 nurses. Data analysis used is multiple linear regression analysis